2016
DOI: 10.1111/2041-210x.12662
|View full text |Cite
|
Sign up to set email alerts
|

EDAPHOLOG monitoring system: automatic, real‐time detection of soil microarthropods

Abstract: Summary Soil microarthropods as organic matter decomposers play an important role in soil functioning thus providing ecosystem services. However, ecosystem scale investigations on their abundance and dynamics are scarce because their high spatio‐temporal heterogeneity requires huge sample size. Processing and identifying large number of individuals are extremely labour‐intensive. We prototyped a device called EDAPHOLOG monitoring system that consists of (1) a probe that catches and detects microarthropods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…The detectability of soil-dwelling and surface-living invertebrates varies with different body shapes, sizes, and appendages (e.g., hairs, scales), which was already observed in our previous study [35].…”
Section: Detection Accuracy Of Irsr-2 For Small Arthropodssupporting
confidence: 75%
See 3 more Smart Citations
“…The detectability of soil-dwelling and surface-living invertebrates varies with different body shapes, sizes, and appendages (e.g., hairs, scales), which was already observed in our previous study [35].…”
Section: Detection Accuracy Of Irsr-2 For Small Arthropodssupporting
confidence: 75%
“…However, the accuracy of detection depends on the size, shape, and even on the movement pattern of the given specimen [11]. In our previous work [35,36], we found that the morphology of arthropods (pigmentation, color, hairs, and appendages) influenced the detectability. These differences in detectability could be seen in the current experiments as well.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Previously, the so-called EDAPHOLOG probe was developed to reduce energy consumption and human effort and to gain more information about the activity of soil-dwelling microarthropods [20]. In this probe, an infrared (IR) sensor was optimized for detecting soil-living microarthropods [21].…”
Section: Introductionmentioning
confidence: 99%